Variants in TSPYL1 are not associated with sudden infant death syndrome in a cohort of deceased infants from Switzerland. Issue 1 (February 2015) - Schubert, Stephanie; Haas, Cordula; Bartsch, Christine; Mirshekarnejad, Mandana; Kohrs, Sarah; Roettinger, Irene; Grosshennig, Anika; Stuhrmann, Manfred; Scholz, Caroline; Schmidtke, Jörg
Abstract: Sudden infant death syndrome (SIDS) is currently the major cause of an unexpected and unexplained death of infants in the first year of lifetime in industrialized countries. Besides environmental factors also genetic factors have been identified as risk factors for SIDS. Notably, the mutation c.457dupG (p.Glu153Glyfs*17) in the TSPYL1 gene has been reported to cause autosomal recessive sudden infant death with dysgenesis of the testes syndrome (SIDDT) in an Old Order Amish community in Pennsylvania. The purpose of this study was to analyze whether variants of TSPYL1 are associated with the sudden infant death syndrome (SIDS) in the area of Europe from which the Amish descended. Mutation analysis of the entire TSPYL1 gene was performed in a cohort of 165 SIDS cases with mostly Swiss ethnic origin, in comparison to 163 German controls. Eight known polymorphisms were detected, none of which was significantly associated with SIDS. One deceased girl was heterozygous for the hitherto unreported TSPYL1 variant c.106C>G (p.Leu36Val), and two affected girls were heterozygous for the rare known TSPYL1 variant rs140756663 (c.1098C>A, p.Phe366Leu). In addition, one deceased boy was heterozygous for the rare common silent nucleotide substitution c.718C>T (p.Leu240Leu, rs150144081), while one control was heterozygous for the rare silent nucleotide substitution rs56190632 (c.760C>T; p.Leu254Leu). In silico analyses predicted a likely non-pathogenic effect for p.Leu36Val and p.Phe366Leu, respectively, although protein features might be affected. The Amish founder mutation was not detected in the analyzed SIDS cases and controls. Mutations and polymorphisms in the TSPYL1 gene were not associated with SIDS in a cohort of 165 deceased Swiss infants.